사이버작전 상황도 구현을 위한 사이버 심볼 연구동향 및 발전방향 - 이종관(Jongkwan Lee); 이민우(Minwoo Lee); 권구형(Koohyung Kwon); 고장혁(Janghyuk Kauh); 오행록(Haengrok Oh); 김선형(Sonyong Kim) (디지털콘텐츠학회논문지, 2021)
본 논문은 사이버작전 상황도 구현을 위한 사이버 심볼 연구 동향을 분석하고 한국군 사이버작전 상황을 고려한 사이버 심볼의 발전방향을 제시한다. 사이버 공간에서의 취약점을 이용한 군사적, 경제적 위협이 지속적으로 증대함에 따라 사이버전 역량 강화에 대한 관심이 크게 증대되고 있다. 이에 따라 효과적인 사이버작전 수행을 위한 사이버작전 상황도의 필요성이 최근 제기되고 있다. 그런데 사이버 작전은 물리적 작전과 근본적으로 다른 특성을 갖고 있으므로 물리적 작전을 위해 현재 사용되고 있는 작전 상황도와 군사심볼을 사이버 작전에 그대로 적용하는 것은 제한적이다. 이에 따라 본 논문은 이러한 제한사항을 극복하기 위한 다양한 연구 동향을 분석하고 사이버 심볼의 발전 방향을 제시하였으며, 이는 한국군의 사이버 심볼 표준화 및 사이버작전 상황도의 효과적 구현에 기여할 수 있을 것으로 기대된다. We analyze the research trends related to a common operational picture for cyber operations and suggest development direction. As military and economic threats using cyberspace vulnerabilities continue, interest in improving cyber capabilities and preparing for cyber warfare is increasing. Meanwhile, the need for a common operational picture for cyber operations has recently been raised. However, since cyber operations are fundamentally different from kinetic operations, it is limited to using the existing military symbols and common operational picture. We analyze the various research to overcome these limitations and suggest the development direction, including cyber symbol standardization issues. We expect that our research result will contribute to the standardization of cyber symbols of the Korean military and the effective implementation of the cyber operational pictures. KCI Citation Count: 0